2015
DOI: 10.3889/oamjms.2015.088
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium lactis in Treatment of Children with Acute Diarrhea. A Randomized Double Blind Controlled Trial

Abstract: BACKGROUND:Probiotics are becoming increasingly popular treatment for children diarrhea. Although there are several probiotic strains potentially useful, researches were often limited to certain strains.AIM:To test Bifidobacterium lactis on morbidity of acute diarrhea in children less than 2 years.SUBJECTS AND METHODS:A randomized double-blind controlled clinical trial was conducted in 50 children (1 - 23 months) admitted with acute diarrhea to the Pediatric Hospital, Cairo University and were randomly assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 28 publications
0
12
0
3
Order By: Relevance
“…Furthermore, the use of regular yogurt in diarrheal disorders has a traditional history among people across many countries. Several research teams investigated the effects of regular yogurt and reported its positive effects on the management of diarrhea [37,38]. Pashapour and Iou found that regular yogurt was effective in improving the clinical outcomes of infants with diarrhea in terms of their hospital stay duration, frequency of diarrhea, and weight loss [37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of regular yogurt in diarrheal disorders has a traditional history among people across many countries. Several research teams investigated the effects of regular yogurt and reported its positive effects on the management of diarrhea [37,38]. Pashapour and Iou found that regular yogurt was effective in improving the clinical outcomes of infants with diarrhea in terms of their hospital stay duration, frequency of diarrhea, and weight loss [37].…”
Section: Discussionmentioning
confidence: 99%
“…Selected members of the genus Bifidobacterium are believed to exert health benefits to the host, including competitive exclusion of pathogens (6,7), modulation of the immune system (8,9), and degradation of diet-derived carbohydrates (10). On the basis of these effects, bifidobacteria are often added to probiotic products in combination with other lactic acid bacteria to prevent or treat diseases (11,12), although the evidence is inadequate. Nevertheless, a growing number of inpatients in U.S. hospitals often receive probiotics as part of their care (13).…”
mentioning
confidence: 99%
“…Терапия заболеваний, сопровождающихся диареей, включает прежде всего этиотропную и патогенетическую терапию, затем -назначение препаратов, купирующих основные симптомы заболевания, в том числе и диарею. Из методов симптоматической терапии рекомендованы диетотерапия, назначение регидратационных препаратов, ферментотерапия, пробиотики, энтеросорбция [5][6][7].…”
Section: роль адсорбентов в купировании синдрома диареи у детеéunclassified